Pendampingan Pengisian dan Pelaporan SPT Tahun PPh Wajib Pajak Orang Pribadi dengan Menggunakan E-Filling - Umar Yeni Suyanto; Rita Nataliawati; Laelatul Zahro (Universitas Muhammadiyah Manado, 2025)
In principle, every individual who fulfills his subjective and objective obligations is obliged to register himself as a Taxpayer (WP) based on the